Development and Validation of Analytical Method for Artemether by HPLC - Arun, R.; Anton Smith, A. (Asian Journal of Chemistry, 2010)
This paper describes the development and validation of a HPLC method (254 nm) for the quantitation of artemether in pure form and pharmaceutical formulations. The method showed to be linear (r2 > 0.99), precise (RSD < 9.73 %), accurate (recovery of 99.83 % for artemether), specific and robust. Three batches of artemether capsules were assayed by the validated method. The artemether contents in the capsules varied from 99.12-100.65 %.